Redesign of a Fried Shallot Oil Draining Machine with a Capacity of 1 kg - Muhammad Gilang Rifky Anugrah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to improve the performance and stability of a 1 kg capacity fried onion oil drainer (spinner) used by MSMEs. The main problems with conventional machines include excessive vibration at high speeds, a less sturdy frame, and the absence of a rotational speed regulator, which reduces draining effectiveness. The method used is engineering design through the stages of literature study, redesign, manufacturing, assembly, and performance testing. The redesign was carried out by strengthening the frame using hollow iron, adding rubber pads as vibration dampers, and installing a dimmer on a 135 watt AC electric motor. Tests were carried out at speeds of 800 rpm, 1200 rpm, and 1400 rpm with a draining time of 10 seconds. The test results showed that the redesigned machine had better performance and stability. Optimum performance was obtained at a speed of 1400 rpm with 206 grams of drained oil and a final weight of fried onions of 775 grams. The redesign was proven to be effective in increasing draining effectiveness and reducing engine vibration at high speeds.